Some Syllabi Descriptions: Strengths and Weaknesses - Aida Bastidas; Vicente Araujo (Asociación Colombiana de Profesores de Ingles, 2016)
When designing a "syllabus" at the beginning of a course or semester, we find some difficulties concerning the appropriate selection of the type of syllabus we want to develop through the course. This selection implies that we have to consider several aspects such as the students' needs, the institution policy, the syllabus, the instructional resources among others.